2010
DOI: 10.1038/nrendo.2010.169
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin for primary prevention of cardiovascular disease in diabetes mellitus

Abstract: Aspirin is effective for the prevention of cardiovascular events in patients with a history of vascular disease, as so-called secondary prevention. In general populations with no history of previous myocardial infarction or stroke, aspirin also seems useful for primary prevention of cardiovascular events, although the absolute benefits are smaller than those seen in patients with previous cardiovascular disease. Patients with diabetes mellitus are at an increased risk of cardiovascular events, but new trials h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 68 publications
1
24
0
Order By: Relevance
“…However, a recent meta-analysis has not confirmed these findings [49]. Nevertheless, aspirin is effective for the prevention of cardiovascular events in patients with a history of vascular disease and it is reasonable to consider aspirin as one of the potential therapies for cardiovascular disease risk reduction in patients with DM and elevated cardiovascular disease risk [50].…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent meta-analysis has not confirmed these findings [49]. Nevertheless, aspirin is effective for the prevention of cardiovascular events in patients with a history of vascular disease and it is reasonable to consider aspirin as one of the potential therapies for cardiovascular disease risk reduction in patients with DM and elevated cardiovascular disease risk [50].…”
Section: Discussionmentioning
confidence: 99%
“…27 In patients with diabetes mellitus, however, the JPAD2 study could not demonstrate the benefit of aspirin for primary prevention. Meta-analyses in patients with diabetes mellitus have reported that aspirin has a smaller benefit for primary prevention than in general populations, 26,28,29 although patients with diabetes mellitus are at high risk for cardiovascular events. It seems that there are differential effects of low-dose aspirin therapy on preventing cardiovascular events in patients with and without diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…7 Inhibition of platelet responsiveness with aspirin therapy reduces the relative risk of myocardial infarction and stroke by about 10%. 8 We demonstrated earlier that insulin inhibits aggregation/secretion by platelets and tissue factor synthesis by monocytes. In healthy individuals, insulin interferes with the suppression of cAMP and accumulation of this inhibitor attenuates platelet functions and monocyte responses.…”
Section: Introductionmentioning
confidence: 99%